Peningkatan Pengetahuan Tentang Infeksi Parasit Penyebab Diare dan Sanitasi Lingkungan - Suriyani Tan; Machrumnizar Machrumnizar (CV. Multi Kreasi Media, 2023)
Diarrhea in one of the leading causes of child mortality worldwide. According to World Health Organization data, there are about 1,7 billion cases of diarrhea in children. Diarrhea due to parasitic infection is widespread throughout developing countries. This includes limited access to health services, socio-economic problems, population density, slum settlements, malnutrition, geographic factors, poor hygiene and waste management, including lack of access to clean water and sanitation.